Productividad del pasto cuba om-22 (Pennisetum purpureum x Pennisetum glaucum) con fertilización de dos abonos orgánicos en Yurimaguas - Rengifo Rios, Jackeline del Pilar (2025)
This research was conducted at CIIEY-UNAP km 17 to determine the productivity of Cuba OM-22 pasture fertilized with two organic fertilizers. The treatments evaluated were (T1 without fertilizer; T2 cow manure 2 kg/m2; T3 chicken manure 2 kg/m2; T4 cow manure 4 kg/m2; and T5 chicken manure 4 kg/m2), with 4 replicates each. The design used was Completely Randomized Blocks (CRB). The results showed that chicken manure was the most effective fertilizer. T5 reached the highest pasture height (2.30 m), significantly surpassing T1 (1.29 m) and all treatments with cow manure. Regarding biomass production, T5 obtained the highest values in green matter (102.35 Tn/ha) and dry matter (26.17 Tn/ha), with statistically significant differences compared to the other treatments. Regarding nutrient content, T5 had the highest values for phosphorus (0.42%) and crude protein (8.83%). Potassium content was highest in T4 (2.48%), significantly different from T1. There were no statistically significant differences in tiller number, cover percentage, calcium, or nitrogen content, although the latter showed a slight upward trend with the use of organic fertilizer, particularly in T5 (1.41% nitrogen). It is concluded that T5 significantly improves the forage yield and phosphorus content of Cuba OM-22 grass, while cow manure showed more limited and less consistent positive effects. These results support the use of chicken manure as an effective and sustainable strategy for increasing pasture productivity and quality in agricultural systems.